Nitrogen and Potassium Applications on the Growth of Amorphophallus muelleri Blume - Edi Santoso (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Productivity of Amorphophallus muelleri is considered low. Thus, pot experiment was conducted at the CikabayanExperimental Farm, Bogor Indonesia during rainy season November 2007 to July 2008, in order to determine the optimumfertilizer dose for A. muelleri under 50% shading net. Treatments consisted of four doses of nitrogen (0, 50, 100 and 150 kgha-1 N) and three doses of potassium (0, 50 and 100 kg ha-1 K2O). The results showed that application of N and K fertilizerssignificantly increased vegetative growth, i.e., number of leaves, number of leaflets and second leaf size, but did not affectharvesting time. Fresh weight and dry matter content of daughter corm were significantly affected by N and K applications.Combination of 50 kg ha-1 N and 100 kg ha-1 K2O resulted in higher corm weight than other treatments. It is evident that theapplication of nitrogen and potassium is important in A. muelleri.Keywords: disease infection, iles-iles, Indonesian konjac, nitrogen, potassium